LOW PHYSICAL AGGRESSION BUT HIGH EMOTIONAL REACTIVITY: A MIXED-METHODS ANALYSIS OF PRESCHOOL CHILDREN’S SELF-REGULATION - Pepi Nuroniah; Rina Nurhudi Ramdhani; Dominikus David Biondi Situmorang; Deri Hendriawan; Ahman Ahman (Jurnal Konseling Pendidikan Islam, 2026)
Aggressive behavior begins to emerge in early childhood as part of social-emotional development and is closely associated with self-regulation capacity. If not appropriately addressed, aggressive behavior may persist and have negative implications for later academic success. This study aimed to (1) describe the profile of aggressive behavior in preschool children and (2) explore this profile in relation to children’s self-regulation abilities based on teachers’ observations. This study employed a mixed-methods design using a concurrent embedded model. The research population consisted of 877 children aged 4–6 years, with total population sampling applied. Quantitative data were collected using an aggressiveness scale, while qualitative data were obtained through in-depth interviews with five teachers selected based on children classified in the moderate and high aggression categories. Quantitative data were analyzed using descriptive statistics, whereas qualitative data were analyzed through thematic analysis. The findings indicate that aggressive behavior among children was generally low, with 63.4% of children classified in the low aggression category and only one child in the high aggression category. Emotional aggression—such as anger, crying, and expressions of dislike—was the most dominant form. Children’s aggression was predominantly reactive, triggered by frustration, peer conflict, competition over toys, or unmet desires. Verbal and physical aggression emerged in specific contexts, particularly among children with lower self-regulation abilities.